Analisis Kepuasan Pengguna Dalam Menggunakan Rekam Medis Elektronik - Farhansyah, Fani; Alfiansyah (CV. Multi Kreasi Media, 2025)
In health care facilities, an evaluation of the use of information technology systems is needed to identify several shortcomings in the use of electronic medical records. Evaluation is carried out so that the information system used can provide optimal service. Evaluation of electronic medical records is carried out to identify weaknesses in the system after use. From the results of the initial study that has been conducted, it is known that at the Sungai Panas Health Center, an evaluation of the use of Electronic Medical Records has not been carried out. Officers who use Electronic Medical Records have also not received training related to the system. This study aims to determine the level of user satisfaction in using EMR at the Sungai Panas Health Center. This study uses a quantitative descriptive method with a research design based on a cross-sectional approach. The subjects of the study were those who used Electronic Medical Records, while the object of the study was the Electronic Medical Records system at the research location. Data were collected through the distribution of questionnaires, with the questionnaire as a research instrument. The results showed that the level of satisfaction of EMR users based on several aspects was in the very satisfied category. From the content aspect, an average value (mean) of 4.68 was obtained, the accuracy aspect got a mean value of 4.6, and the display aspect (format) had a mean value of 4.75. Thus, it can be concluded that user satisfaction with the use of RME at Sungai Panas Health Center is classified as very satisfactory.